PERKEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DI INDONESIA (ANALISIS TUJUAN DAN MATERI AJAR KURIKULUM 1994, 2004, 2006, 2013) - Maherlina Muna Ayuhana (Tarbawi : Jurnal Pendidikan Islam, 2015)
In the wake of this study: Islamic education provided by primary schools have only emphasizes the cognitive domain alone. This condition makes education in Indonesia just scored generation of academics versed in knowledge, but do not have the character in accordance with the values contained in Pancasila which resulted in national education curricula experienced some development. The purpose of this study to uncover the theoretical characteristics of the development of Islamic education curriculum Primary Schools in Indonesia through the objective and content of the curriculum teaching material Islamic Education Primary Schools in Indonesia in 1994, 2004, 2006, 2013. This study is a qualitative research that is research kepustakaaan ( library research) using the historical approach. The technique used for data collection is the documentation and review of the literature. Data analysis technique, researchers used content analysis method. The result of research indicating that: first, the purpose of the learning curriculum Islamic education from 1994 to 2013 of the same essence, that provide basic capabilities to students about Islam to develop a religious life so that a man of Muslim faith and fear of Allah, as well as the noble as individuals, community members, citizens, and human beings. Second, the charge of teaching materials each year to experience growth and a reduction in accordance with the needs of learners and the changing times